2001
DOI: 10.1073/pnas.261455698
|View full text |Cite
|
Sign up to set email alerts
|

neurogenin2 elicits the genesis of retinal neurons from cultures of nonneural cells

Abstract: neurogenin2 (ngn2) encodes a basic helix-loop-helix transcription factor and plays an important role in neurogenesis from migratory neural crest cells. Its role in retinal development is poorly understood. We observed that in the developing chick retina, ngn2 was expressed in a subpopulation of proliferating progenitor cells. Ectopic expression of ngn2 in nonneural, retinal pigment epithelial cell culture triggered de novo generation of cells that expressed neural-specific markers and exhibited neuronal morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 41 publications
2
55
0
Order By: Relevance
“…In fact, our previous studies showed that cultured RPE cells are responsive to the proneural activities of ngn2 and neuroD and may undergo neural transdifferentiation. Furthermore, the types of cells produced by RPE transdifferentiation agree with the retinal expression patterns of the proneural genes Wang, 1998, 2000b;Yan et al, 2001;Ma et al, 2004). In light of all this, RPE transdifferentiation toward retinal neurons might, at least to a certain extent, recapitulate the molecular events of retinal neurogenesis and offer an effective assay for proneural activities.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In fact, our previous studies showed that cultured RPE cells are responsive to the proneural activities of ngn2 and neuroD and may undergo neural transdifferentiation. Furthermore, the types of cells produced by RPE transdifferentiation agree with the retinal expression patterns of the proneural genes Wang, 1998, 2000b;Yan et al, 2001;Ma et al, 2004). In light of all this, RPE transdifferentiation toward retinal neurons might, at least to a certain extent, recapitulate the molecular events of retinal neurogenesis and offer an effective assay for proneural activities.…”
Section: Discussionmentioning
confidence: 60%
“…Previously we have shown that cultured RPE cells are responsive to the proneural activities of ngn2 and neuroD, and they may undergo transdifferentiation into cells that resemble photoreceptors and RGCs Wang 1998, 2000a,b;Yan et al, 2001). We found previously that retroviral-driven ectopic expression of chick ath5 promoted bFGF-initiated RPE transdifferentiation toward RGCs but alone was insufficient to induce such transdifferentiation .…”
Section: Induction Of Rpe Transdifferentiation Toward Photoreceptor Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of neurogenesis in Drosophila demonstrate that Delta is regulated by proneural bHLH transcription factors such as acheate-scute or atonal (reviewed by Skeath and Carroll, 1994;Bertrand et al, 2002). Many bHLH homologs are expressed in the vertebrate retina, but only Ascl1 and Neurog2 are expressed in mitotically active progenitors (Jasoni et al, 1994;Jasoni and Reh, 1996;Perron et al, 1998;Yan et al, 2001;Marquardt, et al, 2001;Ma and Wang, 2006;Le et al, 2006;Nelson and Reh, 2008). While the functions of proneural bHLH genes have been extensively investigated with respect to their role in retinal cell fate specification (reviewed by Cepko, 1999;Vetter and Brown, 2001;Yan et al, 2005;Ohsawa and Kageyama, 2007;Harada et al, 2007), their function in the regulation Notch ligands have not been described in the developing retina.…”
Section: Conserved Ascl1/delta-like/notch/hes Molecular Circuitry In mentioning
confidence: 99%
“…The production and purification of viruses was done as described elsewhere (Yan and Wang, 1998;Yan et al, 2001). …”
Section: Virusesmentioning
confidence: 99%